The impact of pre- and postnatal exposures on allergy related diseases in childhood: a controlled multicentre intervention study in primary health care - Dotterud Christian Kvikne; Storrø Ola; Simpson Melanie Rae; Johnsen Roar; Øien Torbjørn (BMC, 2013)
Abstract Background Environmental factors such as tobacco exposure, indoor climate and diet are known to be involved in the development of allergy related diseases. The aim was to determine the impact of altered exposure to these factors during pregnancy and infancy on the incidence of allergy related diseases at 2 years of age. Methods Children from a non-selected population of mothers were recruited to a controlled, multicenter intervention study in primary health care. The interventions were an increased maternal and infant intake of n-3 PUFAs and oily fish, reduced parental smoking, and reduced indoor dampness during pregnancy and the children's first 2 years of life. Questionnaires on baseline data and exposures, and health were collected at 2 years of age. Results The prevalence of smoking amongst the mothers and fathers was approximately halved at 2 years of age in the intervention cohort compared to the control cohort. The intake of n-3 PUFA supplement and oily fish among the children in the intervention cohort was increased. There was no significant change for indoor dampness. The odds ratio for the incidence of asthma was 0.72 (95% CI, 0.55-0.93; NNTb 53), and 0.75 for the use of asthma medication (95% CI, 0.58-0.96). The odds ratio for asthma among girls was 0.41 (95% CI 0.24-0.70; NNTb 32), and for boys 0.93 (95% CI 0.68-1.26). There were no significant change for wheeze and atopic dermatitis. Conclusion Reduced tobacco exposure and increased intake of oily fish during pregnancy and early childhood may be effective in reducing the incidence of asthma at 2 years of age. The differential impact in boys and girls indicates that the pathophysiology of asthma may depend on the sex of the children. Trial registration Current Controlled Trials ISRCTN28090297.